Analisis Analisis Penentuan Nilai Pasar Wajar Saham: Studi Kasus Right Issue PT Bank Mayapada Internasional Tbk. - Saputro, Diky (Politeknik Keuangan Negara STAN, 2024)
The purpose of this study is to analyze the fair value of PT Bank Mayapada Internasional Tbk (MAYA) shares that conduct corporate action Limited Public Offering XII or right issue which can be used by investors as a reference for making investment decisions. The main data used in this study are financial statement data published by the company on the Indonesia Stock Exchange website. While the supporting data used is macroeconomic and financial data on the banking industry obtained from the Central Statistics Agency (BPS), Bank Indonesia, and Damodaran. Fair value analysis uses the Discounted Cash Flow valuation method and the Guideline Publicly Traded Company. The results of this study found that the fair value of MAYA shares when the right issue was held was IDR 3,026. The exercise price of the rights issue is IDR 2,200 and the market price is IDR 9,100, so there is an opportunity for the difference between the exercise price and fair value with a potential increase of 37.5%. While the market price and fair value there is a difference with a potential decrease of 66.7%.